A stochastic simulation algorithm for Bayesian model updating of linear structural dynamic system with non-classical damping - Cheung, Sai Hung (2014)
Model updating using measured system dynamic response has a wide range of applications in structural health monitoring and control, response prediction, reliability and risk assessment. In this paper, we are interested in model updating of a linear structural dynamic system with non-classical damping based on incomplete modal data including modal frequencies, damping ratios and partial complex mode shapes of some of the dominant modes. To quantify the uncertainties and plausibility of the model parameters, a Bayesian approach is considered in which the probability distribution of the model parameters needs to be updated.A new stochastic simulation algorithm is proposed, which allows for an efficient update of the probability distribution of the model parameters. The effectiveness and efficiency of the proposed method are illustrated by a numerical example involving linear structural dynamic system with complex modes.